The Constitutionality of Age Requirements for Presidential and Vice-Presidential Candidates: Konstitusionalitas Pengaturan Usia Calon Presiden Dan Wakil Presiden - Muhammad Hanif Mahsabihul Ardhi; Wahyu Priyanka Nata Permana (Universitas Islam Indonesia, 2024)
Ahead of the 2024 presidential and vice presidential elections, a number of parties have submitted a judicial review of Article 169 letter q of the Election Law regarding the minimum age requirements for presidential and vice presidential candidates to the Constitutional Court. This research aims to provide an in-depth interpretation of the minimum age requirements for presidential and vice presidential candidates by using a type of normative legal research with the six modalities of constitutional argumentation approach proposed by Philipp Bobbit and using secondary legal materials. The conclusion of this research shows that based on textual, historical and structural arguments, the minimum age requirement for presidential and vice presidential candidates has no other interpretation other than what is stated in the laws, whereas based on doctrinal, prudential and ethical arguments, Article 169 letter q regarding the minimum age requirements for presidential and vice presidential candidates is an open legal policy which is entirely the responsibility of law-making officials to regulate it, apart from that, changes to this article will have a more negative impact on the sustainability of the Constitutional Court.Keywords: Age of Presidential and Vice Presidential Candidates, Constitutional Interpretation, Legal Interpretation, Constitutional Court AbstrakMenjelang pemilihan presiden dan wakil presiden tahun 2024, sejumlah pihak mengajukan uji materi Pasal 169 huruf q UU Pemilu mengenai ketentuan syarat minimal usia calon presiden dan wakil presiden ke Mahkamah Konstitusi. Penelitian ini bertujuan untuk memberikan penafsiran yang mendalam mengenai syarat minimal usia calon presiden dan wakil presiden dengan menggunakan jenis penelitian hukum normatif dengan pendekatan enam modalitas argumentasi konstitusional yang dikemukakan oleh Philipp Bobbit dan menggunakan bahan hukum sekunder. Kesimpulan penelitian menunjukan berdasarkan argumentasi tekstual, historis dan struktral ketentuan syarat minimal usia calon presiden dan wakil presiden tidak memiliki penafsiran lain selain apa yang tertera dalam bunyi undang – undang, sedangkan berdasarkan argumentasi doktrinal, prudential dan etika Pasal 169 huruf q mengenai syarat minimal usia calon presiden dan wakil presiden merupakan kebijakan hukum terbuka yang sepenuhnya merupakan wewenang pembentuk undang – undang untuk mengaturnya. Perubahan terhadap pasal tersebut lebih banyak berdampak negatif terhadap keberlangsungan Mahkamah Konstitusi.Kata Kunci: Usia Calon Presiden dan Wakil Presiden, Penafsiran Konstitusi, Penafsiran Hukum, Mahkamah Konstitusi